Anchoring via covalent binding of a salicylaldimine-nickel complex in multi-walled carbon nanotubes and its application in ethylene oligomerization. Issue 13 (2nd July 2020) - Li, Cuiqin; Zhai, Xue; Cheng, Ming; Li, Yang; Li, Nian; Li, Feng; Wang, Jun
Abstract: Silylated-salicylaldimine nickel(II) (1 ) was synthesized with 3-aminopropyl-trimethoxysilane, salicylaldimine and NiCl2 ·6H2 O, and carbon nanotube-supported salicylaldimine-nickel catalyst (2 ) was synthesized by anchoring 1 covalently to multi-walled carbon nanotubes. The chemical structure of the synthesized ligand was characterized by elemental analysis, 1 H NMR and FT-IR. Compounds were characterized by XRD, FT-IR, TGA and XPS and were used as precatalysts for ethylene oligomerization. The catalytic activity and the selectivity of C6 olefin for 2 were much higher than those for 1 in ethylene oligomerization. Compared with other cocatalysts, the catalytic activity and selectivity to C6 olefin for 2 were the highest using MAO as cocatalyst. When Al/Ni molar ratio was 700, at 25 °C, 30 min and pressure was 0.5 MPa, the catalytic activity of 5.85 × 10 6 g·(mol Ni·h) −1 and selectivity of 94.7% toward C6 olefin for 2 in cyclohexane were observed. Compared with 1, catalyst 2 had the good repeatability and thermal stability, with catalytic activity of 4.29 × 10 6 g·(mol Ni·h) −1 and the selectivity of C6 olefin was 84.3% after the third oligomerization reaction. GRAPHICAL ABSTRACT: